Cinta Yang Terbatas : Telaah Qs. Albaqarah 221 Tentang Cinta Nikah Beda Agama - Muhammad Baihaqi; Edi Hermanto (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Interfaith relationships among the younger generation are increasingly seen as a social phenomenon considered normal amidst digital culture, social media, and modern narratives of tolerance. Love is positioned as a personal right that is often considered free from religious boundaries. This study aims to examine the concept of "limited love" in Surah Al-Baqarah verse 221 as the Qur'an's response to the phenomenon of interfaith marriage that is rampant in the Gen Z era. The method in this study uses a qualitative library research approach, primary data sources in the form of the Qur'an and classical and contemporary commentaries, as well as secondary data from journals, books, and legal regulations in Indonesia. The results show that Surah Al-Baqarah verse 221 emphasizes that faith is the main foundation in marriage, while love, physical attraction, and social status are limited by the values ​​of faith. Amid the flow of normalization of interfaith love in the digital space, this verse remains relevant as a guideline in maintaining the balance between freedom of choice of partner and spiritual responsibility in Islam.